MEDIA VIDEO PEMBELAJARAN DASAR PENGOPERASIAN KAMERA DIGITAL SINGLE LENS REFLEX BERBASIS VIDEOSCRIBE PADA MATA KULIAH FOTOGRAFI DIGITAL DI PROGRAM STUDI S1 PENDIDKAN TEKNIK ELEKTRO UNDIKSHA - I Gede Ardi Darmawan; Nyoman Santiyadnya; I Putu Suka Arsa (Universitas Pendidikan Ganesha, 2021)
This study aims to create a learning video media for the operation of a Digital Single Lens Reflex camera, knowing, and knowing the responses of students or students to the basic learning video media for the operation of a Digital Single Lens Reflex camera. This research belongs to the type of Research and Development (R&D) research. This study uses data analysis with the right proportions using the expert test questionnaire and media expert test, while for the small group test and large group, the test uses the analysis of the Standard Five data model. The study used a questionnaire as data collection by content experts (materials), media experts, and students. The results of the study were obtained: 1) the creation of basic learning video media for the operation of the Digital Single Lens Reflex camera, 2) the results of the media expert validation obtained a percentage of 100% with very decent qualifications and the expert validation results obtained 90.38% with very decent qualifications, 3) the results of the small group trial obtained a very high category, 4) the results of the large group trial obtained the very high category. Results Based on the research, the basic learning video media for the operation of the Digital Single Lens Reflex camera is suitable for use in the learning process for the Digital Photography course at the Undiksha Electrical Engineering Education Study Program.